Isolation, integration, and ethnic boundaries in rural Guatemala - Pebley, Anne R. (2005)
We investigate two perspectives about the effects of reduced discrimination and greater social and economic opportunities on ethnic identity in rural areas of contemporary Guatemala. Our analysis contrasts the effects of new opportunities in Indigenous communities on language use and dress, using data from the 1995 Encuesta Guatemalteca de Salud Familiar (EGSF). While the use of both dress and language has changed substantially in recent years, language use has changed considerably more than dress. We conclude that, in this context, economic opportunities have not necessarily diminished ethnic solidarity, but may have instead reshaped it.